Back Cover. Issue 7 (1st March 2023) - Unknown
Abstract : Herein, we describe a strategy for shaping metal‐organic frameworks (MOFs) with high performance in the capture of carbon dioxide. We have developed a pellet‐shaped ultramicroporous MOF using polyvinyl butyral (PVB) as a binder that has high CO2 adsorption capacity and selectivity for CO2 /N2 and CO2 /CO. Under dynamic flow conditions, this material effectively separates CO2 /N2 or CO2 /CO mixtures, and it can be synthesized at a kilogram scale in a single process. Our research has potential for industrial applications in CO2 capture. More details are discussed in the article by Yang et al . on page 763—768. Abstract : Herein, we describe a strategy for shaping metal‐organic frameworks (MOFs) with high performance in the capture of carbon dioxide. We have developed a pellet‐shaped ultramicroporous MOF using polyvinyl butyral (PVB) as a binder that has high CO2 adsorption capacity and selectivity for CO2 /N2 and CO2 /CO. Under dynamic flow conditions, this material effectively separates CO2 /N2 or CO2 /CO mixtures, and it can be synthesized at a kilogram scale in a single process. Our research has potential for industrial applications in CO2 capture. More details are discussed in the article by Yang et al . on page 763—768.